2009
DOI: 10.1002/elan.200804529
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and Selective Electrochemical Analysis of Methyl‐parathion (MPT) and 4‐Nitrophenol (PNP) by a New Type p‐NiTSPc/p‐PPD Coated Carbon Fiber Microelectrode (CFME)

Abstract: A novel modified carbon fiber microelectrode (CFME) was obtained by combination of tetrasulfonated nickel phtalocyanine (p-NiTSPc) electroformed film associated to para-phenylenediamine (p-PPD) electropolymerized outer-coating. The modified CFMEs where denoted C/p-NiTSPc and C/p-NiTSPc/p-PPD, respectively. These electrodes are dedicated to the organophosphates compounds (OPs) methyl-parathion (MPT) and para-nitrophenol (PNP). Our contribution shows that both OPs can be determined simultaneously on the unmodifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
60
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 43 publications
9
60
0
1
Order By: Relevance
“…These sensitive tools permit the determination of the residues of glyphosate in soils following its treatment by Glyphonet SL 360 formulation with a precision close to previous study but more efficient, sensitive and mainly low cost and rapid. In perspective, we will pursue this study by increasing the sensitivity of CFME using a surface modification as we reported recently (Tapsoba et al, 2009). …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…These sensitive tools permit the determination of the residues of glyphosate in soils following its treatment by Glyphonet SL 360 formulation with a precision close to previous study but more efficient, sensitive and mainly low cost and rapid. In perspective, we will pursue this study by increasing the sensitivity of CFME using a surface modification as we reported recently (Tapsoba et al, 2009). …”
Section: Resultsmentioning
confidence: 93%
“…We previously demonstrated the possibility of carbon fiber microelectrode use, modified or not by tetrasulfonated nickel phtalocyanine to follow parathion methyl and its stable byproducts such as p-nitrophenol (Tapsoba et al, 2009;. In order to determine the most suitable conditions for glyphosate residues determination in soils based on carbon fiber microelectrode, we optimized the square wave voltammetry parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to limit the impact of pesticides on the environment and human health, analytical techniques have been developed to detect their presence and quantify pesticide residues in waters, soils, foods. The commonly used analytical methods are the high-performance liquid chromatography (HPLC), mass spectrometry (MS), gas chromatography (GC) or coupled techniques GC-MS and ELISA [3] [4] [6] [7]. However, these techniques require means huge, skilled technicians, very long analysis time, a step of sample pretreatment and they are not suitable for analysis of organophosphate pesticides due to their instability.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(p-phenylenediamine) can be chemically or electrochemically deposited on surfaces or particles and it is often incorporated in sensors such as glucose sensors [32], H 2 O 2 sensors [33] or nitrophenol sensors [34]. When compared to the large number of papers that have been written on the electropolymerization of aniline it is clear that relatively little work has been done on the polymerization of pphenylenediamine.…”
Section: Introductionmentioning
confidence: 99%